2020
DOI: 10.48550/arxiv.2012.07811
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding Type Ia Supernova Distance Biases by Simulating Spectral Variations

J. D. R. Pierel,
D. O. Jones,
M. Dai
et al.

Abstract: In the next decade, transient searches from the Vera C. Rubin Observatory and the Nancy Grace Roman Space Telescope will increase the sample of known Type Ia Supernovae (SN Ia) from ∼10 3 to 10 5 . With this reduction of statistical uncertainties on cosmological measurements, new methods are needed to reduce systematic uncertainties. Characterizing the underlying spectroscopic evolution of SN Ia remains a major systematic uncertainty in current cosmological analyses, motivating a new simulation tool for the ne… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 49 publications
(93 reference statements)
0
7
0
Order By: Relevance
“…Understanding the origin of these sample differences, whether they are related to selection effects or not, is of clear importance. Pierel et al (2020) show that, if uncorrected, the HR offset between velocity subsamples found by S20 could be a leading systematic uncertainty in future supernova surveys aiming at precision cosmology, such as from the Nancy Grace Roman Space Telescope (Hounsell et al 2018). If, on the other hand, supernova cosmology samples are more similar to the Foundation objects, the effect may be muted.…”
Section: Hubble Residualsmentioning
confidence: 88%
“…Understanding the origin of these sample differences, whether they are related to selection effects or not, is of clear importance. Pierel et al (2020) show that, if uncorrected, the HR offset between velocity subsamples found by S20 could be a leading systematic uncertainty in future supernova surveys aiming at precision cosmology, such as from the Nancy Grace Roman Space Telescope (Hounsell et al 2018). If, on the other hand, supernova cosmology samples are more similar to the Foundation objects, the effect may be muted.…”
Section: Hubble Residualsmentioning
confidence: 88%
“…This simulation does not exactly reproduce the data set because of random fluctuations in photometric noise and intrinsic scatter, and also because the underlying SALT2 model formalism is an approximation as discussed in Pierel et al (2020). Nonetheless the simulation is very similar to the data and is therefore sufficient for testing SALTshaker, as illustrated in Figure 3 for a representative low-z SN Ia.…”
Section: Simulated Jla Training Samplementioning
confidence: 96%
“…As regularization can bias the model surfaces by over-smoothing them (Mosher et al 2014), we tune the weights to ensure that the regularization terms do not contribute significantly to the total χ 2 . Further work to determine how this regularization scheme affects the model and to choose optimal model configurations will require applying our training and analysis framework to simulations (Dai et al in prep;Pierel et al 2020).…”
Section: Regularizationmentioning
confidence: 99%
See 2 more Smart Citations